PRAKONSENTRASI DAN ANALISIS RENIK CU2+ BERBASIS ANALISIS INJEKSI ALIR MENGGUNAKAN XAD-16 TERMODIFIKASI PYROCATHECOL VIOLET - Prasetyo, Heru
Preconcentration method and flow injection analysis based copper trace analysis are based on the retention of Cu2+ ion in polystiren divinylbenzen (XAD-16) modified by Pyrocathecol Violet (PV), by using Flame Atomic Absorption Spectrometer (FAAS) as a detector. PV was retented well in pH 4 with the retention capacity of 0,7896 mg PV / gram XAD-16. The analysis of Cu2+ ion retention in XAD-16 / PV in pH 5 was carried out by two method, the batch method and the column saturation level method. Analysis by the batch method resulted in the retention capacity of 0,6540 mg Cu2+ / gram XAD-16/PV, while the analysis by the column saturation level method resulted in the retention capacity of 0,0196 mg Cu2+ / gram XAD-16/PV. The minimum volume of 1M HNO3 for quantitative elution copper is 0,5 mL. Analytical performance of this developed method showed a good precision (%CV= 1,36) with limit detection = 7,66 ?g L-1, sensitivity = 1,20 ?g L-1), and sample recovery = 105,27 %.